Quaternion-Based Attitude Tracking Control Design for UAVs - Lin, Qain-Rong; Yu, Jen-Te (CACS International Automatic Control Conference (Online), 2024)
This paper utilizes quaternions to represent the attitude of UAVs and proposes an attitude controller. We use backstepping methodology together with fractional exponent to achieve salient performance in tracking a desired attitude trajectory. Numerical simulation results are provided to verify the presented scheme and demonstrate itseffectiveness.